Grazing cattle on alfalfa - D. Hayes; L. Corah; E.E. Bartley (Kansas Agricultural Experiment Station Research Reports, 1980)
Data collected from six producers grazing 4050 head of cattle on 850 acres of irrigated alfalfa showed that under optimum conditions, Kansas producers can expect: stocking rate, 5 to 6 head/acre; average daily gain, 2 lbs +; total pounds of beef/acre, 1300 to 1500 lbs; and death loss below 1%. Bloat Guard 2,3 performed the best when added to a grain supplement.
Keywords: Cattlemen' s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Alfalfa